2020
DOI: 10.1177/0269881120972336
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of attention deficit/hyperactivity disorder in individuals with autism spectrum disorder: A systematic review of the literature

Abstract: Aim: To assess the empirical evidence for the treatment of attention deficit/hyperactivity disorder (ADHD) in populations with autism spectrum disorder (ASD). Methods: A systemic PubMed, PsychINFO, Embase, and Medline database search of peer-reviewed literature was conducted. Included in the review were controlled trials published in English with sample sizes ⩾10 participants examining the safety and efficacy of anti-ADHD medication in ASD populations. Data was extracted on relevant variables of study design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The final dose of ATX in this case was 120 mg/day, which was at the acceptable upper end of the adult ATX dosage range (37). Pediatric study has shown that atomoxetine for ADHD with comorbid ASD produced gastrointestinal side effects in most cases (38), but no significant side effects were observed in this case.…”
Section: Discussionmentioning
confidence: 75%
“…The final dose of ATX in this case was 120 mg/day, which was at the acceptable upper end of the adult ATX dosage range (37). Pediatric study has shown that atomoxetine for ADHD with comorbid ASD produced gastrointestinal side effects in most cases (38), but no significant side effects were observed in this case.…”
Section: Discussionmentioning
confidence: 75%
“…When describing how CBT didn’t work for them, one autistic adult said, “[the provider] expected me to be neurotypical, so I would take things too literally and they thought it was a defense mechanism, or I’d try to explain meltdowns and they focused on my thoughts rather than how to deal with over-reactive sensory perception [ 14 ••].” Other autistic adults may have difficulty with receptive and/or expressive language; one parent of an autistic adult described how their son “gets overwhelmed with too much verbal input” and, as a result, was discharged from mental healthcare that relied heavily on group therapy and talking [ 40 ] . Traditional pharmacotherapy approaches for managing conditions such as ADHD or obsessive–compulsive disorder (OCD) may be less effective for some autistic people [ 21 , 41 ]. Consideration of different medications or types of therapy in these situations is essential for success.…”
Section: Autistic Adults’ Use Of Mental Healthcare Servicesmentioning
confidence: 99%
“…Other autistic adults may have difficulty with receptive and/or expressive language; one parent of an autistic adult described how their son "gets overwhelmed with too much verbal input" and, as a result, was discharged from mental healthcare that relied heavily on group therapy and talking [40]. Traditional pharmacotherapy approaches for managing conditions such as ADHD or obsessivecompulsive disorder (OCD) may be less effective for some autistic people [21,41]. Consideration of different medications or types of therapy in these situations is essential for success.…”
Section: Rigid Approaches To Carementioning
confidence: 99%
“…Systematic reviews in which all relevant studies were captured in other more recent or more comprehensive systematic reviews were excluded. [6][7][8][9][10][11][12][13][14] Primary studies retrieved by the search were excluded if they were captured in 1 or more included systematic reviews. 15 Guidelines with unclear methodology were also excluded.…”
Section: Exclusion Criteriamentioning
confidence: 99%